Pedophiles Are Not Always Child-Molesters: A Literature Review on the Virtuous Pedophiles Community - Tan, Tiffany; Poerwandari, Elizabeth Kristi (Bulletin of Counseling and Psychotherapy, 2025)
Pedophiles, individuals who are sexually attracted to children, are regarded as child-molesters. This stigma incites hate and discrimination towards them, even those who have not and committed themselves to not harm children. Thus, understanding and challenging this stigma is important to help them. In this study, we explored the experience of members of Virtuous Pedophiles, an online support group and the preferred identity for pedophiles who are against sexual activity between adults and children. Narrative literature review and thematic analyses were conducted on Gary Gibson’s book titled Virtuous Pedophiles. Virtuous Pedophiles, unfortunately, encounter problems in their daily life, yet they choose to acknowledge and share their sexual orientation with loved ones. They also develop various strategies to protect themselves and children from any form of molestation. They build boundaries in interacting with children, avoid situations involving children, and use fantasy in the form of pornography and masturbation to satisfy their sexual needs without harming children. They hope the stigma on pedophiles is reduced and one day, they can live comfortably by receiving help and support from others and mental health practitioners. Despite acknowledging their sexual orientation, they are still experiencing difficulties in fully accepting themselves due to the stigmatization experienced from others and concerns about their own future. This also hinders them in reaching out for help from professional services to manage their overall wellbeing. As mental health practitioners, we are encouraged to focus more on their psychological distress and then devise strategies that might help improve their daily functioning.